2005
DOI: 10.1007/s00134-005-2588-2
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar fibrinolytic capacity suppressed by injurious mechanical ventilation

Abstract: Alveolar fibrinolytic capacity is suppressed during mechanical ventilation with high pressure amplitudes due to local production of PAI-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…33 A previous murine model of lung fibrogenesis caused by injurious mechanical ventilation showed that TGF-b1 induced the production of PAI-1 and administering PAI-1 RNA interference inhibited EMT and the progression of pulmonary fibrogenesis. 8,9,15 TGF-b1 can inhibit collagen degradation by inducing PAI-1 expression and thus inhibiting the activities of plasmin and tPA. 15 We demonstrated that high-V T mechanical ventilation increased lung injury, collagen deposition, fibroblast accumulation, increased expression of mesenchymal markers a-SMA and type I collagen, but decreased epithelial marker ZO-1, and PAI-1 and TGF-b1 production.…”
Section: Discussionmentioning
confidence: 99%
“…33 A previous murine model of lung fibrogenesis caused by injurious mechanical ventilation showed that TGF-b1 induced the production of PAI-1 and administering PAI-1 RNA interference inhibited EMT and the progression of pulmonary fibrogenesis. 8,9,15 TGF-b1 can inhibit collagen degradation by inducing PAI-1 expression and thus inhibiting the activities of plasmin and tPA. 15 We demonstrated that high-V T mechanical ventilation increased lung injury, collagen deposition, fibroblast accumulation, increased expression of mesenchymal markers a-SMA and type I collagen, but decreased epithelial marker ZO-1, and PAI-1 and TGF-b1 production.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that in models of VILI, local pulmonary fibrinolysis is suppressed during injurious mechanical ventilation known as ventilator-associated coagulopathy [12,13]. However, the models used were iatrogenic in nature, either a single exposure to lipopolysaccharide [13] or fibrin deposits caused by human plasma without inflammation [12].…”
mentioning
confidence: 99%
“…However, the models used were iatrogenic in nature, either a single exposure to lipopolysaccharide [13] or fibrin deposits caused by human plasma without inflammation [12]. Furthermore, in neither of these models was systemic analysis performed.…”
mentioning
confidence: 99%
“…Studies of animal models of VILI showed that high tidal volume ventilation increases alveolar fibrin deposition and systemic PAI-1 activity while lungprotective mechanical ventilation decreases BALF levels of PAI-1, attenuates coagulation, and enhances fibrinolysis [14,21] . Although aerosol administration offers the theoretical advantage of the lungs receiving high concentrations of tPA, we chose intravenous administration because intra-alveolar and intravascular fibrin deposition and high systemic PAI-1 levels are frequently found in the setting of acute lung injury or VILI [5,15] . Intraperitoneal tPA lavage could also reduce intraabdominal PAI-1 concentrations in experimental peritonitis [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary fibrin turnover, the deposition of fibrin in the alveolar space, and increased procoagulant activity of bronchoalveolar lavage fluid (BALF) are the pathognomonic features of VILI [5,6] . Alveolar fibrin deposition may lead to surfactant dysfunction, poor gas exchange, decreased lung compliance, and increased ventilatory dependence [7] .…”
Section: Introductionmentioning
confidence: 99%